The genetic diversity in a South American Dwarf Caiman (Paleosuchus palpebrosus) is structured by landscape features - Beatriz Diogo Vasconcelos (2022)
The distribution of species and the way that populations are structured is the result of intrinsic historical processes of the species and their relationships with landscape features. Studies with different aquatic and semi-aquatic organisms show how their distribution and genetic structure are shaped by landscape features and climatic suitability. Paleosuchus palpebrosus is one of the smallest crocodilians in the world and has a wide distribution with different habitat conditions. Here, we investigate how elements of landscape heterogeneity impact genetic differentiation and evaluate the evolutionary and phylogeographic history of the species. The three lineages recovered brought unique information about the genetic structure of the species for other areas where we reported genetic data for the first time. Part of the genetic differentiation resulted from spatial distance coupled with isolation by resistance. Furthermore, our historical demography analysis for this species found a recent history and no changes on effective population sizes through time, differently from what happened with the vast majority of the Neotropical fauna during the Pliocene and Pleistocene. Our findings highlight the main drivers for the evolutionary history of the species and how landscape features can shape the diversification, especially if we consider rivers as a facilitator of gene flow.